Pharmacological actions of dieckol on modulation of platelet functions and thrombus formation via integrin αIIbβ3 and cAMP signaling - Muhammad Irfan; Tae-Hyung Kwon; Hyuk-Woo Kwon; Man Hee Rhee (Elsevier, 2022)
Background and purpose: Dieckol is a phlorotannin that can be found in seaweeds, particularly in Eisenia bicyclis (brown algae) and is known to have anti-oxidant, anti-inflammatory, and anti-microbial properties. It also possesses anti-thrombotic and pro-fibrinolytic activities; however, the mechanistic aspects of anti-platelet and anti-thrombotic activity are yet to be explored. Study design and methodology: We investigated the pharmacological effects of dieckol on the modulation of platelet functions using human, rat, and mice models. Inhibitory effects of dieckol on platelet aggregation were assessed using platelet-rich plasma and washed platelets, followed by measurement of dense granule secretions, fibrinogen binding to integrin αIIbβ3, fibronectin adhesion assay, platelet spreading on immobilized fibrinogen, and clot retraction. Cyclic nucleotide signaling events were evaluated, such as cyclic-AMP production followed by vasodilator-stimulated phosphoprotein (VASP) stimulation. The in vivo anti-thrombotic potential was evaluated in mice using an acute pulmonary thromboembolism model and tail bleeding assay. Results: Dieckol markedly inhibited platelet aggregation and granule secretion; furthermore, it down-regulated integrin αIIbβ3-mediated inside-out and outside-in signaling events, including platelet adhesion, spreading, and clot retraction, whereas it upregulated the cAMP-PKA-VASP pathway. Dieckol-treated mice significantly survived the thrombosis than vehicle treated mice, without affecting hemostasis. Histological examinations of lungs revealed minimum occluded vasculature in dieckol-treated mice. Conclusion: Dieckol possesses strong anti-platelet and anti-thrombotic properties and is a potential therapeutic drug candidate to treat and prevent platelet-related cardiovascular disorders.